Pengenalan Marketplace pada UMKM “Rengginang Cap Mawar” Kelurahan Plosokerep Sebagai Upaya Peningkatan Daya Jual - Yumna Putri Salsabil; Fauzatul Laily Nisa; Marseto Marseto (LPPM Universitas Dharma Andalas, 2022)
The internet is one of the basic needs that cannot be separated by most people, with the development of the internet, a technology in the economic field called E-commerce has emerged. One of the media to bring together sellers and buyers in E-commerce is the marketplace. The most popular marketplace in Indonesia is Shopee. This service is aimed at introducting the use of the Shopee application so that it can be used by MSME